Crystallization and preliminary neutron diffraction experiment of human farnesyl pyrophosphate synthase complexed with risedronate. Issue 4 (1st April 2014) - Yokoyama, Takeshi; Ostermann, Andreas; Mizuguchi, Mineyuki; Niimura, Nobuo; Schrader, Tobias E.; Tanaka, Ichiro
<x xml:space="preserve">Abstract</x> Nitrogen‐containing bisphosphonates (N‐BPs), such as risedronate and zoledronate, are currently used as a clinical drug for bone‐resorption diseases and are potent inhibitors of farnesyl pyrophosphate synthase (FPPS). X‐ray crystallographic analyses of FPPS with N‐BPs have revealed that N‐BPs bind to FPPS with three magnesium ions and several water molecules. To understand the structural characteristics of N‐BPs bound to FPPS, including H atoms and hydration by water, neutron diffraction studies were initiated using BIODIFF at the Heinz Maier‐Leibnitz Zentrum (MLZ). FPPS–risedronate complex crystals of approximate dimensions 2.8 × 2.5 × 1.5 mm (∼3.5 mm3) were obtained by repeated macro‐seeding. Monochromatic neutron diffraction data were collected to 2.4 Å resolution with 98.4% overall completeness. Here, the first successful neutron data collection from FPPS in complex with N‐BPs is reported.